2014
DOI: 10.1371/journal.pone.0093691
|View full text |Cite
|
Sign up to set email alerts
|

Single Rapamycin Administration Induces Prolonged Downward Shift in Defended Body Weight in Rats

Abstract: Manipulation of body weight set point may be an effective weight loss and maintenance strategy as the homeostatic mechanism governing energy balance remains intact even in obese conditions and counters the effort to lose weight. However, how the set point is determined is not well understood. We show that a single injection of rapamycin (RAP), an mTOR inhibitor, is sufficient to shift the set point in rats. Intraperitoneal RAP decreased food intake and daily weight gain for several days, but surprisingly, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 25 publications
8
33
0
Order By: Relevance
“…Consistent with previous investigations, 4,5,16,17) rapamycin was demonstrated to decrease the body weights of the high-fat diet-induced fatty mice. Moreover, mice in Rap group had significantly reduced tissue weights of gWAT and scWAT, which was in accordance with previous study that chronic rapamycin treatment impaired lipid deposition, reduced adiposity and fat cell number in rats.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous investigations, 4,5,16,17) rapamycin was demonstrated to decrease the body weights of the high-fat diet-induced fatty mice. Moreover, mice in Rap group had significantly reduced tissue weights of gWAT and scWAT, which was in accordance with previous study that chronic rapamycin treatment impaired lipid deposition, reduced adiposity and fat cell number in rats.…”
Section: Discussionsupporting
confidence: 91%
“…S6K1, downstream of mTOR, protects against age- and diet-induced obesity in mice [36]. Furthermore, single intraperitoneal RP led to decreased food intake and daily weight gain [37], both of which may offer a potential explanation for the consistent inhibitory effect of RP on weight gain. Animals that were administered CQ also lost weight throughout the 4-week period with a concomitant reduction in food consumed (data not shown), which is consistent with a previous study [38].…”
Section: Discussionmentioning
confidence: 99%
“…If LIF induces malaise, the animals are expected to later display aversion to the flavor associated with the LIF injection. We have previously used this test and showed that lithium chloride induces conditioned taste aversion to saccharin as expected . On the conditioning day, rats were given access to a novel 0.1% saccharin solution for 1 h and then immediately injected i.c.v.…”
Section: Resultsmentioning
confidence: 88%